2023
DOI: 10.3390/pharmaceutics15020461
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 Mediates Dendritic-Cell-Derived Exosome Migration and Improves Cardiac Function after Myocardial Infarction

Abstract: Dendritic cells (DCs) play key roles in promoting wound healing after myocardial infarction (MI). Our previous studies have shown that exosomes derived from DCs (DEXs) could migrate to lymphoid tissue and improve cardiac function post-MI by activating CD4+ T cells; however, the mechanism of DEXs’ migration to lymphoid tissue and the improvement of cardiac function are still unknown. In our study, we found that CCR7 expression significantly increased in MI-DEXs compared with control-DEXs; meanwhile, CCL19 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Some studies have shown that extracellular vesicles exerted a better therapeutic efficacy than the cells releasing the EVs [ 6 ]. At present, abundant sources of membrane vesicles have been developed, including various biological fluids (e.g., blood, milk [ 7 , 8 ], orange juice [ 9 ]), animal cells (e.g., mesenchymal stem/stromal cells (MSCs) [ 7 , 10 , 11 ], dendritic cells [ 12 ], macrophages [ 13 ], tumor cells [ 14 ], red blood cells [ 15 ], different animal cell lines [ 16 ], and others), plant cells (e.g., grapes, conifers, ginger, garlic, tea, etc.) [ 17 ], bacteria (e.g., intestinal flora and probiotics) [ 18 , 19 , 20 ], and others [ 21 , 22 ].…”
Section: Sources Of Membrane Vesicles For Ddssmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have shown that extracellular vesicles exerted a better therapeutic efficacy than the cells releasing the EVs [ 6 ]. At present, abundant sources of membrane vesicles have been developed, including various biological fluids (e.g., blood, milk [ 7 , 8 ], orange juice [ 9 ]), animal cells (e.g., mesenchymal stem/stromal cells (MSCs) [ 7 , 10 , 11 ], dendritic cells [ 12 ], macrophages [ 13 ], tumor cells [ 14 ], red blood cells [ 15 ], different animal cell lines [ 16 ], and others), plant cells (e.g., grapes, conifers, ginger, garlic, tea, etc.) [ 17 ], bacteria (e.g., intestinal flora and probiotics) [ 18 , 19 , 20 ], and others [ 21 , 22 ].…”
Section: Sources Of Membrane Vesicles For Ddssmentioning
confidence: 99%
“…The frequently used methods include differential ultrafiltration centrifugation (dUC), density gradient centrifugation, ultrafiltration (UF), precipitation, dimensional exclusion chromatography (SEC), and immunoaffinity capture, as well as emerging technologies (e.g., microfluidic) [ 6 ]. In this Special Issue, commercial ExoQuick-Tc TM Exosome Precipitation Solution was used for the isolation of dendritic cell-derived exosomes [ 12 ] and of human cell-secreted EVs [ 16 ]; differential ultracentrifugation method was used to separate EVs from mesenchymal/stromal stem cells [ 7 ] or from orange ( Citrus sinensis ) juice [ 9 ]; and density gradient centrifugation method was also utilized to prepare milk EVs [ 7 ].…”
Section: Preparation and Modification Of Membrane Vesicles As Ddssmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy can reveal the double layer capsule structure of exosomes. Exosome surface markers, including CD63, CD81, CD9, TGS101, HSP70, and Alix, can be identified by using Western blot (WB). , …”
Section: Introductionmentioning
confidence: 99%